A high-efficiency PEG-Ca2+-mediated transient transformation system for broccoli protoplasts - Yang, Dongxu; Zhao, Yongyu; Liu, Yumei; Han, Fengqing; Li, Zhansheng (Frontiers in Plant Science, 2022)
Transient transformation of plant protoplasts is an important method for studying gene function, subcellular localization and plant morphological development. In this study, an efficient transient transformation system was established by optimizing the plasmid concentration, PEG4000 mass concentration and genotype selection, key factors that affect transformation efficiency, and an efficient and universal broccoli protoplast isolation system was established. Using 0.5% (w/v) cellulase R-10 and 0.1% (w/v) pectolyase Y-23 to hydrolyze broccoli cotyledons of three different genotypes for 3.0 h, the yield was more than 5×106/mL/g, and the viability was more than 95%, sufficient to meet the high standards for protoplasts to be used in various experiments. The average transformation efficiencies of the three plasmid vectors PHG-eGFP and CP507-YFP in broccoli B1 protoplasts were 61.4%and 41.7%, respectively. Using this system, we successfully performed subcellular localization of the products of three target genes (the clubroot resistance gene CRa and two key genes regulated by glucosinolates, Bol029100 and Bol031350); the results showed that the products of all three genes were localized in the nucleus. The high-efficiency transient transformation system for broccoli protoplasts constructed in this study makes it possible to reliably acquire high-viability protoplasts in high yield. This research provides important technical support for international frontier research fields such as single-cell sequencing, spatial transcriptomics, plant somatic hybridization, gene function analysis and subcellular localization.